Rupture of a peritoneal hydatid cyst: Rare cause of acute intestinal obstruction - Tayeb Ben Tayeb; Ajdar Hicham; Alaoui Othman; Mahmoudi Abdelhalim; Khattala Khalid; Bouabdallah Youssef (Elsevier, 2022)
Intraperitoneal rupture of the primary peritoneal hydatid cyst with an intact proligerous membrane is rare. We report the case of a 5-year-old girl who had consulted for febrile occlusive syndrome. Abdominal scan without injection found mechanical obstruction without finding the cause. Surgical exploration found a univesicular hydatid cyst of the peritoneum in the right iliac fossa ruptured with an intact proligerous membrane and blocked by the intestinal loops. The aim of this work is to report a new case of intraperitoneal rupture of a hydatid cyst with intact proligerous membrane and to specify the diagnostic and therapeutic difficulties met during this complication.